Answer:
(x, y) = (-8, -3)
Step-by-step explanation:
If all you want is a quick solution, I find a graphing calculator to be very handy. The one used in the attachment shows the solution to be (x, y) = (-8, -3).
_____
You can use one equation to substitute for y in the other equation:
-3x -27 = 5 +x
-32 = 4x . . . . . . add 3x-5 to both sides
-8 = x . . . . . . . . divide by 4
y = 5 +(-8) = -3 . . . . . use the second equation to find y
The pair of numbers that satisfies both equations is ...
(x, y) = (-8, -3)